PHYTOCHEMICAL, ANTIOXIDANT AND ANTIBACTERIAL STUDIES ON THE LEAF EXTRACTS OF CURCUMA AMADA ROXB - George, Mariat; Britto, S. John (International Journal of Current Pharmaceutical Research, 2016)
Objective: This study investigates the chemical composition, in vitro antioxidant activity and antibacterial activity of leaf extract of Curcumaamada Methods: GC-MS analysis of these extracts was performed using a Perkin-Elmer GC Clarus 500 system. The antioxidant activity was done by using 2, 2-Diphenyl-1-picrylhydrazyl (DPPH) radical, total antioxidant assay, Ferric reducing power assay, Hydrogen peroxide scavenging activity, and nitric oxide scavenging assay. Evaluation of in vitro antibacterial activity was carried out by the disc diffusion method. Thirteen bacterial strains were used in this study. Results: The GC-MS analysis of the ethanolic extracts has shown a profile of 15 compounds. The antioxidant study proves that the leaf extracts could serve as an important bio-resource of antioxidants for the pharmaceutical industry. The extracts of leaf remarkably inhibited the growth of 13 bacterial strains Conclusion: This study revealed that phytochemicals compound present in ethanolic extract, antioxidant properties of ethanol and acetone extract and antimicrobial activity.